Field evaluation and calibration of Tensiometer and Gypsum block sensors in drip irrigated Broccoli (Brassica oleracea var. italica) - KUMARI, ARTI; PATEL, NEELAM; MISHRA, A. K. (Journal of Soil and Water Conservation, 2020)
Field and laboratory experiments were carried out during November to February 2015-16 at Precision Farming Development Centre, Water Technology Centre, IARI, New Delhi to study the field evaluation and calibration of soil moisture sensors (tensiometers and gypsum blocks) in drip irrigated broccoli (Brassica oleracea var. italica).The experiment included three levels of irrigation frequencies: N1 (once every day), N2 (once every 2 days) and N3 (once every 3 days) with three irrigation levels of 100, 80 and 60 % of crop evapotranspiration (ETc).For evaluating the performance of different soil moisture sensors, the sensors’ readings were taken from plot on daily basis and these readings were compared with those obtained from the gravimetric method. It was observed that the calibration of two sensors (Tensiometers and Gypsum blocks) give the similar calibration equation, having a quite low RMSE and ensuring good performances after field calibration. The value of coefficient of determination (R2) for Gypsum block was estimated as 0.76, 0.83, 0.84 and 0.85 for 0-15, 15-30, 30-45 and 45-60 cm soil depths whereas, the value of coefficient of determination (R2) for tensiometers was estimated as 0.84, 0.83, 0.75 and 0.73 for 0- 15, 15-30, 30-45 and 45-60 cm soil depths respectively. The tensiometers were found less responsive to dry conditions than gypsum block sensors whereas gypsum blocks were found less responsive to wet conditions. It was concluded that field calibration of soil moisture sensors are essential for improving to measure the soil moisture content and diurnal soil moisture variations lead to water vapour flux into the soil. It is recommended that field based calibrations developed may be preferred over laboratory based calibrations, since field data are more representative of the situations in the field where sensors were installed.